“Mundo em suspensão” o protagonismo da COIAB diante da pandemia de COVID-19 - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2022)
This work aims to investigate and demonstrate the role of the Coordination of Indigenous Organizations of the Brazilian Amazon (COIAB) in the pandemic period between early 2020 and mid-2022, as well as the strategies used by the organization, along with the actions, that were fundamental to reduce the impacts of covid-19 on the indigenous peoples of the Brazilian Amazon. Among the strategies of struggle, I try to show that the model of organization in networks formed by the internal and external relationship, were essential in this context of resistance against the coronavirus, in order to contain the risk of indigenous genocide. Faced with the colonialist structure of the Brazilian State, under the command of a president who did little to contain the advance of covid-19 in the Brazilian population in general, I bring an excerpt of how the Federal Government was silent and conniving with the violence suffered by indigenous people in the face of pandemic, thus, in this context, indigenous organizations in the country (re)organized themselves and, through constitutional law, managed to force the Federal Government to provide health care to indigenous groups. Thus, I discuss how COIAB was part of this process. Thus, I use the analysis of data from COIAB itself, made available on its digital platforms, as well as data provided by the World Health Organization; from the data made available by the Special Secretariat for Indigenous Health and through bibliographic references that show the research carried out in this context. I conclude that it was due to the articulation of the indigenous movement through legal instruments, such as ADPF-709, defended in the Federal Supreme Court; the use of digital media, through cyber activism; elaboration of protocols to face covid-19 in indigenous peoples; elaboration of projects, in order to obtain financing for the purchase of hygiene materials, protective masks against covid-19, purchase of food products, among others.
Keywords: Movimento indígena; COIAB; COVID-19; Genocídio indígena; Amazônia Brasileira; CNPQ:: CIÊNCIAS HUMANAS